In Antisynthetase Syndrome, ACPA Are Associated With Severe and Erosive Arthritis. Issue 20 (May 2015) - Meyer, Alain; Lefevre, Guillaume; Bierry, Guillaume; Duval, Aurélie; Ottaviani, Sébastien; Meyer, Olivier; Tournadre, Anne; Le Goff, Benoit; Messer, Laurent; Buchdahl, Anne Laure; De Bandt, Michel; Deligny, Christophe; et al.
<x xml:space="preserve">Abstract</x> Abstract Anticitrullinated peptide/protein antibodies (ACPA), which are highly specific for rheumatoid arthritis (RA), may be found in some patients with other systemic autoimmune diseases. The clinical significance of ACPA in patients with antisynthetase syndrome (ASS), a systemic disease characterized by the association of myositis, interstitial lung disease, polyarthralgia, and/or polyarthritis, has not yet been evaluated with regard to phenotype, prognosis, and response to treatment. ACPA-positive ASS patients were first identified among a French multicenter registry of patients with ASS. Additionally, all French rheumatology and internal medicine practitioners registered on the Club Rhumatismes et Inflammation web site were asked to report their observations of ASS patients with ACPA. The 17 collected patients were retrospectively studied using a standardized questionnaire and compared with 34 unselected ACPA-negative ASS patients in a case–control study. All ACPA-positive ASS patients suffered from arthritis versus 41% in the control group (P < 0.0001). The number of swollen joints was significantly higher (7.0 ± 5.0 vs 2.9 ± 3.9, P < 0.005), with a distribution resembling that of RA. Radiographic damages were also more frequent in ACPA-positive ASS patients (87% vs 11%, P < 0.0001). Aside from a significantly higher transfer factor for carbon monoxide in ACPA–ASS patients, lung, muscle, and skin involvements had similar incidences, patterns, and severity in both groups. Although Nonbiologic treatments were similarly used in both groups, ACPA-positive patients received biologics more frequently (59% vs 12%, P < 0.0008), mostly due to refractory arthritis (n = 9). Eight patients received anti-Cluster of differentiation 20 (CD20) monoclonal antibodies (mAbs) with good efficacy and tolerance, whereas 2 of the 5 patients treated with antitumor necrosis factor drugs had worsened myositis and/or interstitial lung disease. After a >7-year mean follow-up, extra-articular outcomes and survival were not different. ACPA-positive ASS patients showed an overlapping RA–ASS syndrome, were at high risk of refractory erosive arthritis, and might experience ASS flare when treated with antitumor necrosis factor drugs. In contrast, other biologics such as anti-CD20 mAb were effective in this context, without worsening systemic involvements.